Development Tendents of the Pension System and Problems of Financial Sustainability - Sh. U. Rajabov (Researchparks Publishing, 2021)
The article analyzes the financial indicators and trends of the state pension system, the main indicators of the non-state pension system, as well as the state of formation and payment of funds of non-state pension funds and draws appropriate conclusions.